Phosphorylation of the actin binding protein drebrin at S647 is regulated by neuronal activity and PTEN - Kreis, Patricia; Hendricusdottir, Rita; Kay, Louise; Papageorgiou, Ismini E.; Diepen, Michiel van; Mack, Till; Ryves, Jonny; Harwood, Adrian; Leslie, Nicholas R.; Kann, Oliver; Parsons, Maddy; Eickholt, Britta (PLOS ONE, 2013)
Defects in actin dynamics affect activity-dependent modulation of synaptic transmission and neuronal plasticity, and can cause cognitive impairment. A salient candidate actin-binding protein linking synaptic dysfunction to cognitive deficits is Drebrin (DBN). However, the specific mode of how DBN is regulated at the central synapse is largely unknown. In this study we identify and characterize the interaction of the PTEN tumor suppressor with DBN. Our results demonstrate that PTEN binds DBN and that this interaction results in the dephosphorylation of a site present in the DBN C-terminus - serine 647. PTEN and pS647-DBN segregate into distinct and complimentary compartments in neurons, supporting the idea that PTEN negatively regulates DBN phosphorylation at this site. We further demonstrate that neuronal activity increases phosphorylation of DBN at S647 in hippocampal neurons in vitro and in ex vivo hippocampus slices exhibiting seizure activity, potentially by inducing rapid dissociation of the PTEN:DBN complex. Our results identify a novel mechanism by which PTEN is required to maintain DBN phosphorylation at dynamic range and signifies an unusual regulation of an actin-binding protein linked to cognitive decline and degenerative conditions at the CNS synapse.
Gesehen am 30.03.2021